Penyuluhan Penyakit Parasiter pada Ternak Ruminansia dan Pelatihan Pembuatan Pupuk Organik di Kelompok Ternak Putra Rahayu, Kabupaten Wonogiri, Jawa Tengah - Yuli Yanti; Wari Pawestri; Dewanto Harjunowibowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Parasitic diseases usually attack cattle or sheep, which can cause a decrease in livestock productivity. One of the parasitic diseases that arise is caused by the cage's cleanliness and poor management of faecal waste. This community engagement activity aims to increase farmers' knowledge about ruminants' parasitic diseases and train them to produce organic fertilizer from cow faeces. The activity was carried out at the Putra Rahayu Cattle Group Farmers in Tawangrejo Village, Jatipurno District, Wonogiri Regency. Activities included conveying information about parasitic diseases and training on making organic fertilizer from cow faeces. This livestock group has 25 members. All participants participated in the activity enthusiastically. As many as 28.6% of respondents already know how to make organic fertilizer. All participants did not know about parasitic diseases. After counselling and training, farmers' knowledge increased by 72.4% about how to make organic fertilizers and increased 100% of their knowledge about parasitic diseases in livestock. The results of the cow faeces test found that Toxocara sp., strongyle and trematode parasite eggs were then given a grant in the form of parasitic drugs for ruminants. This activity concludes that farmers' knowledge of parasitic diseases and organic fertilizers increases.